Understanding large temporal networks and spatial networks exploration, pattern searching, visualization and network evolution - Batagelj, Vladimir., author (Wiley series in computational and quantitative social science, 2014)
This book explores social mechanisms that drive network change and link them to computationally sound models of changing structure to detect patterns. This text identifies the social processes generating these networks and how networks have evolved.